2015
DOI: 10.4050/jahs.60.032009
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Determining the Optimal Rotational Speed of a Variable RPM Main Rotor/Turboshaft Engine System

Abstract: Variable speed rotors represent an innovative research field for the development of new rotorcraft designs. Issues related to employing a main rotor variable speed are numerous and require an interdisciplinary approach. For this reason, a preliminary effort has been made to understand the performance implications of coupling helicopter trim and turboshaft engine simulations. Following this, two different models of a UH-60 Black Hawk helicopter and a GE T700 turboshaft engine are implemented and validated again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Miste et al [2] investigated numerically the performance implications of variable rotor speed for the UH-60A Black Hawk helicopter including the impact of rotor-engine integration. Miste et al noted that incorporating the effect of engine coupling is essential for the determination of the optimum rotor speed for minimum fuel consumption.…”
Section: Variable Rotor Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…Miste et al [2] investigated numerically the performance implications of variable rotor speed for the UH-60A Black Hawk helicopter including the impact of rotor-engine integration. Miste et al noted that incorporating the effect of engine coupling is essential for the determination of the optimum rotor speed for minimum fuel consumption.…”
Section: Variable Rotor Speedmentioning
confidence: 99%
“…Several authors have examined the topics of variable rotor speed and active blade twist in the existing literature [1,2,3]. However, previous researchers have approached these concepts either strictly from an aero-mechanical standpoint [6,9,14,19], or solely from an "isolated-rotor" point of view [5,11,13].…”
Section: Scope Of Present Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing rotor speed in hover and forward flight, has been extensively investigated to save helicopter power and improve helicopter performance [1][2][3][4][5][6][7][8][9]. Kang et al analyzed several rotor morphing concepts, and the comparisons showed that a reduced rotor speed could yield more power savings than other investigated concepts [10].…”
Section: Introductionmentioning
confidence: 99%
“…Misté, Benini and Garavello et al analyzed the variable-speed rotor with a turboshaft engine and optimized the rotor speed based onthe minimal required power and minimal fuel consumption. The results showed that in hover and fast flight, these two optimizations lead to different optimal rotor speeds, and the one based on the required power could not reduce the entire vehicle fuel consumption due to the deterioration in engine efficiency [12]. Then, a continuously variable transmission concept was proposed to solve this problem [13,14].…”
Section: Introductionmentioning
confidence: 99%